Rancang Bangun Sistem Operasi Mode Cutting Monopolar pada Electrosurgery Unit Berbasis ESP 8266 - Suwarmiyati; Soekarman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Electrosurgery Unit (ESU) is widely used in the medical world for surgical procedures that require high accuracy with reduced bleeding. This study aims to design and implement a cutting mode on an ESU based on ESP 8266 with monopolar mode. The system is designed using an oscillator based on CMOS IC CD4069 which produces a high frequency in the range of 300–500 kHz. The test results show that the device is capable of working in three power settings: LOW mode (404 kHz, 8.0% error), MEDIUM mode (450 kHz, 9.0% error), and HIGH mode (500 kHz, 10% error), which provides flexibility according to surgical needs. The unique method applied is the integration between the ESP 8266 microcontroller for precision control and the use of potentiometers for dynamic frequency settings. Although the results show a high success rate, the limitation of the device lies in the focus of the system which only includes cutting mode without additional features such as coagulation or tissue burning. However, this device offers great potential for future development, including integration with IoT for remote monitoring and expansion of operation modes. With a simple yet innovative design, this device is expected to provide an efficient and safe solution for modern surgical needs.